The value of crowdsourcing for creative clusters development - Bogusław Bembenek; Katarzyna Kowalska (ACTA INNOVATIONS, 2016)
The article consists of three integral parts. It characterises the essence of the functioning of creative clusters, the concept of open innovation and crowdsourcing strategic dimension. Considerations presented in the article are focused on the importance of crowdsourcing in the development of creative clusters. The problem of using crowdsourcing to solve complex problems can be evaluated with multiple levels and multiple perspectives. The authors emphasise that this model of communication between cluster members and external stakeholders allows the use of internal and external resources of creativity in the process of co-creation of positive changes, including innovations (e.g. entrepreneurial solutions to local and global new challenges). They indicate that the implementation of the crowdsourcing in creative clusters can have both, a commercial dimension, where new business projects are the result of the transfer of knowledge, and a non-commercial one, for instance, a wider use of this concept in the development of creative spaces. It was stressed that innovativeness is one of the attributes of entrepreneurial orientation of clusters. Moreover, the key barriers to development of open innovation within a cluster environment are different problems related to intellectual property. The article is based on theoretical research (literature review) and on desk research. Considerations contained herein are conceptual and provide a starting point for further research on the impact of crowdsourcing on the open innovation process within creative clusters.